Analisis Yuridis terhadap Sengketa Putusan MK Nomor 90/PUU-XXI/2023 tentang Uji Materi terhadap Pasal 169 Huruf q Undang – Undang Nomor 7 Tahun 2017 tentang Pemilihan Umum (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2025)
The Constitutional Court is a judicial institution in Indonesia which was established on August 13, 2003. The Constitutional Court has the authority regulated in article 24C of the 1945 Constitution and Law Number 24 of 2003 concerning the Constitutional Court which was later updated to Law Number 8 of 2011. The Constitutional Court has a principle in making a decision on the material test of the law against the Constitution, which applies to everyone, final, independent and impartial. The Constitutional Court's (MK) decision regarding the age limit for presidential and vice presidential candidates (presidential and vice presidential candidates) in Case Number 90/PUU-XXI/2023 continues to reap pros and cons. In the decision, the Constitutional Court granted part of the application that tested Article 169 letter q of Law Number 7 of 2017 concerning General Elections. This study aims to identify and analyze disputes over the Constitutional Court Decision Number 90/PUU-XXI/2023 concerning the material test of article 169 letter q of Law number 7 of 2017 concerning general elections in terms of juridical aspects. The research method used is a literature study of the Constitutional Court decision Number 90/PUU-XXI/2023 with a focus on normative legal analysis. The results of the study show that the Constitutional Court's decision Number 90/PUU-XXI/2023 is formally inconsistent with Law Number 49 of 2009 concerning Judicial Power and Constitutional Court Regulation No. 2/PMK/2021.